2018
DOI: 10.19044/esj.2018.v14n3p342
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Survey of Medicinal Plants Used Against Fungal Infections in Prefecture of Sotouboua Central Region, Togo

Abstract: Plants are a major source of active ingredients and are for that fact used to treat many diseases such as fungal infections. The objective of this study was to identify the plants used in traditional medicine to treat fungal diseases in the prefecture of Sotouboua. An ethnobotanical survey was conducted among healers, elderly and knowledgeable villagers. A semi structured questionnaire and pictures showing common and easily recognizable fungal infection symptoms were used to support a live interview. During th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…Most traditional therapists are between 53 and 58 years old with an average age of 60 years, while most herbalists are between 47 and 52 years old with an average age of 55 years. These results are similar to those reported by Koudokpon et al [15] and Gnagne et al [16] and Alfa et al [17] in their work. This shows that the traditional medicine sector is the preserve of middle-aged people who therefore hold the ancestral knowledge transmitted from generation to generation.…”
Section: Discussionsupporting
confidence: 93%
“…Most traditional therapists are between 53 and 58 years old with an average age of 60 years, while most herbalists are between 47 and 52 years old with an average age of 55 years. These results are similar to those reported by Koudokpon et al [15] and Gnagne et al [16] and Alfa et al [17] in their work. This shows that the traditional medicine sector is the preserve of middle-aged people who therefore hold the ancestral knowledge transmitted from generation to generation.…”
Section: Discussionsupporting
confidence: 93%
“…The oral administration of the preparations was the preparation method, the most recommended way of administration. According to many other authors, it is also the route of administration for most herbal preparations both in our study area [ 61 , 67 ] and in other countries [ 70 , 71 , 73 – 75 ].…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, in Benin, the recent work of Koudokpon et al (2017) on plants used in the treatment of infections and that of Fah et al had reached the same conclusions [ 67 , 68 ]. In other area in Africa, several authors in Togo, Nigeria, Congo and South Africa had also found that decoction was the most common preparation method used by traditional healers [ 62 , 54 , 70 , 71 ]. Kinda et al (2017) reports that this method is the most efficient way to extract bioactive compounds from plants [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Africa, most published data and ethnopharmacological surveys related to the anticancer potential of plants were from Cameroon, Ghana, Nigeria, Egypt, Madagascar, Morocco, Algeria, and Ethiopia [13][14][15][16]. In Togo, some ethnopharmacological surveys have been conducted but they have not focused on cancer [17][18][19][20][21]. e ecological and floristic diversity and the presence of an association of traditional healers practicing in the field support the hypothesis of the availability of potential anticancer plants in Togo.…”
Section: Introductionmentioning
confidence: 99%